Simulation of edge cracking using shear GTN damage model during hot plate rolling of magnesium alloys. Issue 1 (1st December 2022) - Zhao, C C; Liu, J L; Li, Z X; Jia, R; Huang, Z Q; Wang, T
Abstract : Edge cracks are a more prominent problem during the rolling process of magnesium alloy sheets. The hexagonal structure of magnesium alloys and the product defects caused by the second phase impurities mixed in the sheets are the main causes of edge cracking. Conventional hot-rolled edge cracking simulations can only characterize the edge damage of the sheets numerically, however, the actual crack morphology is ignored. In this paper, the Gurson-Tvergaard-Needleman (GTN) damage model coupled with a continuous medium shear damage model was developed for improving the applicability of the model at low-stress triaxiality. Powell's "Dogleg" method was used in the numerical solution of the damage model instead of the traditional Newton-Raphson method and the Vumat subroutine was written for the finite element simulation by the stress return algorithm. The damage model parameters were calibrated by a shear specimen. The results showed a good agreement between the simulated crack morphology and the experiment.